Glass fiber hybrid composites molded by RTM Using a dispersion of carbon nanotubes/clay in epoxy - Sene T.S.* (2013)
Nanocomposites based on epoxy and a mixture of clays and multi-walled carbon nanotubes (MWCNT) were produced by casting, and also molded by RTM using glass fibers as reinforcement, yielding a hybrid multi-scale micro/nanocomposite material. Two types of montmorillonite clays were used, natural (MMT-Na) and organophilic (MMT-30B). Higher viscosity was obtained for the mixture with MMT-30B and it was observed that this clay did not perform as well as the MMT-Na in helping the dispersion of the carbon nanotubes (CNT). The glass transition temperature (Tg) of the nanocomposites increased in up to 6°C with the addition of MWCNT and up to 10°C with the addition of MMT-30B, differently from the MMT-Na which did not alter the Tg of the material. By transmission electron microscopy, it was verified that more homogeneous dispersions and more intercalated structures were obtained with the MMT-30B than with the MMT-Na. Finally, the low clay content used and, especially, the very low MWCNT content, did not significantly alter the studied flexural properties. © 2013.